EZENWANYI AS A METAPHOR FOR RELIGION: CHARACTERISATION AND NARRATIVE ACTIONS - Obiyor, Ijeoma Precious (African Journal of Social and Behavioural Sciences, 2024)
Most critical analysis of the character of Ezenwanyi in Akachi Adimora-Ezeigbo’s House of Symbols (2005) read her from the feminist perspective as a strong woman. This is Akachi Adimora-Ezeigbo’s way of challenging the patriarchal structure in the Christian religion and as a bridge in the gap between the traditional African religion and the Christian religion. However, discourse on Ezenwanyi’s character from a different perspective other than feminist theory, sociological theory, and socio-linguist-structuralist theory are yet to be considered. Therefore, this paper attempts to study Ezenwanyi’s character under the topic, Ezenwanyi as a Metaphor for Religion: Characterisation and Narrative Actions in Akachi Adimora-Ezeigbo’s House of Symbols. (2005) from the perspective of Jacques Derrida’s theory on Deconstruction. The aim is to do a deconstructive reading of the character portrayal of Ezenwanyi in Akachi Adimora-Ezeigbo’s House of Symbols (2005) in order to present a rereading of her character presentation as it modifies the understanding of religious practices having in mind the religious strife in our society. The theoretical framework of deconstruction forms the basis of the analysis of the text. Emphasis is laid on the significance of her character and actions in understanding the essence of Traditional African Religion and Christian Religion as to eradicate dissensions among religious groups. The findings reveal Ezenwanyi as a metaphor for religion unravelling the disconnection of modern Africans from their root and ignorance as the cause of the seeming difference in religions. And that religion practiced with a self-adaptive and dynamic mindset promotes peaceful communal living.